Prognostic Factors for Morcellation During Vaginal Hysterectomy. Issue 4 (April 2016) - Wasson, Megan; Butler, Kristina; Magtibay, Paul; Temkit, M'hamed; Magrina, Javier
Abstract : OBJECTIVE: To determine prognostic factors associated with cold-knife morcellation during vaginal hysterectomy. METHODS: We conducted a retrospective cohort study evaluating all consecutive patients undergoing a vaginal hysterectomy between January 1, 2009, and August 31, 2014. The primary outcome was the utilization of uncontained vaginal morcellation performed using cold-knife wedge resection at the time of vaginal hysterectomy. Secondary outcomes included perioperative data. Significant factors were included in a multivariate logistic regression model to the binary variable vaginal morcellation at the time of vaginal hysterectomy. RESULTS: A total of 743 women met study inclusion criteria and underwent vaginal hysterectomy with intact uterine removal (n=383) or with uterine morcellation (n=360) with and without other vaginal procedures. A nonparametric Wilcoxon-rank-sum test and χ 2 test were used to compare the cohorts of patients with and without morcellation. Characteristics associated with significantly increased likelihood of morcellation included younger age, non-Caucasian race, American Society of Anesthesiologists class 1 or 2, lower parity, lower number of prior vaginal deliveries, absence of prolapse, presence of leiomyoma, and an enlarged uterus. A multivariate logistic model utilizing factors most likely associated with morcellation revealed lack of prolapse (adjusted odds ratio [OR] 3.87, P <.001), leiomyoma (adjusted OR 2.77, P =.035), and larger uterine weight (adjusted OR 7.25, P <.001) increased the likelihood of morcellation. Prior vaginal delivery was associated with a decreased likelihood of morcellation (adjusted OR 0.79, P =.005). CONCLUSION: Vaginal hysterectomy with morcellation is associated with the following factors: absence of prior vaginal delivery, absence of prolapse, presence of leiomyoma, and a uterus larger than normal size. Abstract : Factors associated with morcellation at the time of vaginal hysterectomy are absence of prior vaginal delivery, absence of prolapse, presence of leiomyoma, and an enlarged uterus.